“Diminishing returns” and leaf area-biomass scaling of ferns in subtropical ecosystems - Chen, Shubing; Li, Jinlong; Sun, Jun; Zhong, Quanlin; Hu, Dandan; Cheng, Dongliang (Frontiers in Plant Science, 2023)
Foliage leaves are the primary photosynthetic organ of the majority of vascular plants, and their area vs. biomass scaling relationships provide valuable insights into the capacity and investment in light interception, which is critical to plant growth and performance. The "diminishing returns” hypothesis (DRH), which is based primarily on data from gymnosperms and angiosperms, posits that leaf (lamina) area scales with leaf dry mass. However, it remains uncertain whether DRH applies to ferns or whether ecological factors affect the scaling exponents governing fern leaf morphometrics. To address this issue, 182 individuals of 28 subtropical ferns species were studied at low, medium, and high elevations (i.e., 600 m, 900 m, and 1200 m, respectively). The results show that, at the individual plant level, individual leaf area (ILA) did not differ significantly among the three different elevations (P > 0.05). However, individual leaf mass (ILM) was significantly higher at 900m than at 1200m (P < 0.05), resulting in a significantly higher leaf mass per area (LMA) at the 900m elevation than at the 600m and 1200m elevations (P < 0.05). The ILA and ILM at the 900m elevation were significantly higher than at the 600m elevation (P < 0.05). At the species level, ILA and ILM did not differ significantly among the three elevations (P > 0.05). The total leaf area per individual (TLA) did not differ significantly across the different elevations (P > 0.05). However, total leaf mass per individual (TLM) did differ significantly (P < 0.05). At the individual plant level, the scaling exponents for ILA vs. ILM and TLA vs. TLM at the three different elevations were all significantly less than 1.0 (P < 0.05), which was consistent with the DRH. At the species level, the scaling exponents for the ILA vs. ILM were significantly less than 1.0 at the middle and high elevations, but not at the low elevation. These results indicate that the scaling relationships of leaf area versus mass of subtropical ferns at different elevations support the DRH. The study further informs our understanding of the resource allocation strategies of an ancient and diverse plant lineage.